Revelation – Mattan Torah - Benjamin Sommer (St Andrews Encyclopaedia of Theology)
Revelation is a central concept in Judaism, referring broadly to the communication of God’s will. This article addresses Jewish thinking about how God communicates God’s will to the Jewish people and to humanity more generally. It identifies main themes and debates that recur in Judaism, from the biblical era (including traditions that underlie and precede the final form of biblical books) through Rabbinic and medieval traditions and into the modern and contemporary eras. It acknowledges not only the variety of ways Jewish thinkers have perceived the mechanics of revelation but also the ways in which these approaches recognize that different sacred texts (the Pentateuch, other parts of the Bible, Rabbinic texts, post-Rabbinic texts) have been revealed (or influenced by revelational processes) in different ways. Some sacred texts in Judaism are the product of sages’ interpretation of older revealed texts, and the interpretive activities of the sages can be considered part of the revelatory process, which entails both divine and human roles. The article further asks whether Judaism acknowledges a universal revelation based on reason or nature and accessible to all humanity in addition to, and underlying, a particular revelation to Israel. The article ends by examining two feminist approaches to revelation along with the challenges and new models these approaches open up.